Mademoiselle - Richardson, Tony; Watkin, David; Moreau, Jeanne; Manni, Ettore; Skinner, Frank (bfi, 2020)
A suppressed and sociopathic school teacher (Jeanne Moreau) unsuspectedly torments residents of a small French village with acts of violence and destruction. An erotic obsession with an ostracized outsider causes her behavior to become yet more erratic but, as tensions in the community reach boiling point, will the villagers see beyond their prejudices? Apart from the femme-fatale-in-overdrive aspect of this film, it is also visually satisfying in every possible way. Rampant open-air sex - in a thunderstorm - has never looked so good (or so convincing). Natural sound creates more atmosphere than an added soundtrack ever could. Dramatically, it has the long drawn out obsessive tension of a Lady Chatterley (what is it with these woodcutters?) but with much more finely chiseled characters. While Moreau's work here has similarities with her role in "Diary of a Chambermaid", this Mademoiselle is altogether more accessible, more extreme, more downright nasty. [www.dvdbeaver.com]
Keywords: DVD-Video